2017
DOI: 10.2196/mhealth.7236
|View full text |Cite
|
Sign up to set email alerts
|

Assessing User Engagement of an mHealth Intervention: Development and Implementation of the Growing Healthy App Engagement Index

Abstract: BackgroundChildhood obesity is an ongoing problem in developed countries that needs targeted prevention in the youngest age groups. Children in socioeconomically disadvantaged families are most at risk. Mobile health (mHealth) interventions offer a potential route to target these families because of its relatively low cost and high reach. The Growing healthy program was developed to provide evidence-based information on infant feeding from birth to 9 months via app or website. Understanding user engagement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 40 publications
10
101
1
Order By: Relevance
“…Other authors reported retention rates in eHealth interventions ranging from 0.5% (Eysenbach, ) to 93% (Hammersley, Jones, & Okely, ). Therefore, user engagement in mHealth interventions is considered as the main concern of this type of intervention (Taki et al, ). The adolescents' lifestyle changes in both intervention and control groups differed according to the school district.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported retention rates in eHealth interventions ranging from 0.5% (Eysenbach, ) to 93% (Hammersley, Jones, & Okely, ). Therefore, user engagement in mHealth interventions is considered as the main concern of this type of intervention (Taki et al, ). The adolescents' lifestyle changes in both intervention and control groups differed according to the school district.…”
Section: Discussionmentioning
confidence: 99%
“…Our quantitative analysis of app usage [41] revealed higher engagement with the program amongst those recruited by their health practitioner, those who registered when their infant was younger, those who were first time mothers, and those using both the app and website (via email links) compared to those using the app alone. This suggests that to maximise engagement and potential impact, consideration should be given in the future to focus on recruiting first time parents, with the help of health practitioners during the early postnatal or antenatal period.…”
Section: Discussionmentioning
confidence: 90%
“…At 12-week follow-up, user engagement and interaction with the mobile phone app will be quantified using an engagement index [44]. The index is an adapted version of the Web Analytics Demystified Visitor Engagement Index [45].…”
Section: Methodsmentioning
confidence: 99%